(untitled) (Konferensiyalar | Conferences, 2023)
We have three forms of degrees of adjective, positive form is used to describe a single noun or subject without making any comparison. Comparative is used to compare two nouns or subjects, it indicates that one noun or subject has a higher or lower degree of quality described by the adjective compared to other superlative is used to compare three or more nouns or subjects, it indicates one noun or subject has highest or lowest degree of quality described by the adjective compared to all others.